Structural Stabilization of Clinically Oriented Oligomeric Proteins During their Transit through Synthetic Secretory Amyloids - Sanchez, Julieta Maria (2024)
Developing time-sustained drug delivery systems is a main goal in innovative medicines. Inspired by the architecture of secretory granules from the mammalian endocrine system it has generated non-toxic microscale amyloid materials through the coordination between divalent metals and poly-histidine stretches. Like their natural counterparts that keep the functionalities of the assembled protein, those synthetic structures release biologically active proteins during a slow self-disintegration process occurring in vitro and upon in vivo administration. Being these granules formed by a single pure protein species and therefore, chemically homogenous, they act as highly promising time-sustained drug delivery systems. Despite their enormous clinical potential, the nature of the clustering process and the quality of the released protein have been so far neglected issues. By using diverse polypeptide species and their protein-only oligomeric nanoscale versions as convenient models, a conformational rearrangement and a stabilization of the building blocks during their transit through the secretory granules, being the released material structurally distinguishable from the original source is proved here. This fact indicates a dynamic nature of secretory amyloids that act as conformational arrangers rather than as plain, inert protein-recruiting/protein-releasing granular depots.